Bill of Lading in Transporting Goods at Sea to Envisage an Efficiency of Export and Import Transaction - Sudarwanto, AL Sentot; Purwosutedjo, Grace Ayu (Faculty of Law, Universitas Sebelas Maret, 2019)
This study discusses the law of transporting goods at sea by using a document of charge called Bill of Lading known in common law system is from the 16th century. The research is taken based on the empirical type by showing evidence obtained from the field then analyzed based on bibliography and theory which exists. The result of the research is that each of the international regulations studied does not describe explicitly what the rights and obligations of exporters and importers. However, the B/L contract on the back describes the rights and obligations of exporters and importers as